2005
DOI: 10.1124/jpet.104.081901
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Analysis of the Blood-Brain Barrier Transport of125I-Amyloid β Protein 40 in Wild-Type and Alzheimer's Disease Transgenic Mice (APP,PS1) and Its Implications for Amyloid Plaque Formation

Abstract: Amyloid plaques are formed in the extracellular space of Alzheimer's disease (AD) brain due to the accumulation of amyloid ␤ (A␤) proteins such as A␤40. The relationship between A␤40 pharmacokinetics and its accumulation within and clearance from the brain in both wild-type (WT) and AD transgenic mice (APP,PS1) was studied to understand the mechanism of amyloid plaque formation and the potential use of A␤40 as a probe to target and detect amyloid plaques. In both WT and APP,PS1 mice, the 125 I-A␤40 tracer exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 27 publications
10
59
1
Order By: Relevance
“…The participation of LRP-1 in BBB efflux of Ab is supported by the finding that knockdown of LRP-1 in the BBB using antisense oligonucleotides causes impaired Ab efflux, accumulation of Ab in the brains of young, wild-type mice, and cognitive impairments. 54 The association of impaired Ab efflux with AD was substantiated by observations of decreased Ab efflux in rodent models of AD 55,56 as well as in aged squirrel monkeys 57 and in a small sample set of humans with AD. 58 More recently, it has become evident that other transporters in the BBB facilitating Ab efflux also become impaired in AD.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 96%
See 2 more Smart Citations
“…The participation of LRP-1 in BBB efflux of Ab is supported by the finding that knockdown of LRP-1 in the BBB using antisense oligonucleotides causes impaired Ab efflux, accumulation of Ab in the brains of young, wild-type mice, and cognitive impairments. 54 The association of impaired Ab efflux with AD was substantiated by observations of decreased Ab efflux in rodent models of AD 55,56 as well as in aged squirrel monkeys 57 and in a small sample set of humans with AD. 58 More recently, it has become evident that other transporters in the BBB facilitating Ab efflux also become impaired in AD.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 96%
“…85,86 Systemic clearance of Ab is facilitated by the liver and, to a lesser extent, the kidneys and spleen. 55,87 Lipoprotein receptorrelated protein-1 was shown to be the predominant transporter that mediates clearance by the liver. The short half-life of circulating Ab (on the scale of minutes), 55,87 and the capacity of the liver to clear Ab at levels far exceeding its physiologic concentration in blood suggest that there is a biologic necessity to protect against elevations in circulating Ab.…”
Section: Transport Of Amyloid-b Influx and Systemic Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Although the animals were received Aβ intracerebroventricularly, however, via plasma clearance of Aβ, the extract can help to decrease the Aβ level in brain. Since systemic clearance of Aβ, especially by the liver, could determine the plasma levels of Aβ available for transport into the brain across the blood-brain barrier [9,15] it can be concluded that the lavender may undergo the liver clearance of Aβ. However, probable direct effect of the medicine on the Aβ plaques in the brain requires crossing the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms in removing Aβ is mediated by liver and low-density lipoprotein receptorrelated protein (LRP-1) [8,9]. LRP-1 is a receptor for uptaking Aβ through hepatic [10].…”
Section: Introductionmentioning
confidence: 99%